Experimental investigation for the solubilities of 2, 3, 3, 3-tetrafluoroprop-1-ene (R1234yf) in polyol ester, polyvinylether, and polyalkylene glycol base oils. (May 2021) - Jia, Tao; Bi, Shengshan; Wu, Jiangtao; Jiang, Weixue; Li, Panyuan
Highlights: Dimensional synthesis compared four-, six- and eight-bar mechanism gait trainers. Eight-bar configuration had greater kinematic accuracy with constant input velocity. Kinematic accuracy was similar for all mechanisms with well-controlled input. Abstract: Knowledge of the solubility of 2, 3, 3, 3-tetrafluoroprop-1-ene (R1234yf) in lubricant oil is an indispensable factor for designing refrigeration system and choosing suitable lubricant oil. In this work, the solubilities of R1234yf in polyol ester (POE) base oil, polyvinylether (PVE) base oil, and polyalkylene glycol (PAG) base oil were measured in the temperatures range from 273 K to 353 K based on the isochoric method. The experimental solubility data were correlated using the Peng-Robinson (PR) equation of state and Wilson activity coefficient model. The absolute average relative deviations of the experimental data and calculated values for the R1234yf + POE base oil system, R1234yf + PVE base oil system, and the R1234yf + PAG base oil system are 2.47%, 1.66%, and 1.29%, respectively.